2016
DOI: 10.1186/s12906-016-1479-0
|View full text |Cite
|
Sign up to set email alerts
|

Fermented barley and soybean (BS) mixture enhances intestinal barrier function in dextran sulfate sodium (DSS)-induced colitis mouse model

Abstract: BackgroundInflammatory bowel disease (IBD) is characterized by chronic or relapsing immune system activation and inflammation within the gastrointestinal tract. The lack of safety and efficacy of standard therapies, the use of food supplements for managing IBD is increasing, and many studies have reported that various food supplements provide many beneficial effects for the IBD.MethodsThis study aimed to evaluate the anti-colitis effects of dietary supplementation with a fermented barley and soybean mixture (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 30 publications
(28 reference statements)
3
33
0
Order By: Relevance
“…Integrity of intestinal barrier is pivotal for the homeostasis of intestinal immune system. [30][31][32][33] In the current study, myricetin treatment (80 mg/kg) significantly decreased the serum level of complement component 3, but significantly increased the expression levels of tight junction genes, claudin and occludins, in UC mice. These data together suggested that Figure 5 qPCR was used to determine the relative expression levels of gene claudin (a) and occluding (b).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Integrity of intestinal barrier is pivotal for the homeostasis of intestinal immune system. [30][31][32][33] In the current study, myricetin treatment (80 mg/kg) significantly decreased the serum level of complement component 3, but significantly increased the expression levels of tight junction genes, claudin and occludins, in UC mice. These data together suggested that Figure 5 qPCR was used to determine the relative expression levels of gene claudin (a) and occluding (b).…”
Section: Discussionsupporting
confidence: 49%
“…And it has been proposed that intestinal permeability contributes to the pathogenesis of ulcerative colitis. Integrity of intestinal barrier is pivotal for the homeostasis of intestinal immune system . In the current study, myricetin treatment (80 mg/kg) significantly decreased the serum level of complement component 3, but significantly increased the expression levels of tight junction genes, claudin and occludins, in UC mice.…”
Section: Discussionmentioning
confidence: 46%
“…A DSS-induced chronic colitis mouse model was previously reported to recapitulate a number of key processes characteristic to the clinical manifestations of such complex disease as IBD [4]. These include diarrhea, weight loss, intestinal inflammation, immune cells infiltration, and high pro-inflammatory cytokine expression levels during the acute phase of the developing colitis, intestinal barrier disruption, changes in the microflora composition, and some aspects of neurological disorders [5][6][7][8][9]. It has been shown that pro-and anti-inflammatory cytokines play a major role in the development of IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, a mixture of fermented barley and soybean reduced the severity of colitis in a DSS mouse model, reduced FITC‐dextran permeability and increased occludin and claudin‐1 expression (Woo et al . ). L. plantarum ZS2058 producing conjugated linoleic acid (CLA) decreased TNFα, IL‐1β and IL‐6 and increased levels of anti‐inflammatory PPARγ and IL‐10 in a DSS mouse model (Wang et al .…”
Section: Disease States and The Intestinal Barriermentioning
confidence: 97%
“…Caco-2 monolayers co-cultured with differentiated THP-1 cells (macrophages) exposed to LPS and TNFa decreased TEER; however, combination of the probiotic L. plantarum and mannan-oligosaccharides restored TEER, increased IL-6 and -10 levels and decreased TNFa production (Brufau et al 2016). Similarly, a mixture of fermented barley and soybean reduced the severity of colitis in a DSS mouse model, reduced FITC-dextran permeability and increased occludin and claudin-1 expression (Woo et al 2016). L. plantarum ZS2058 producing conjugated linoleic acid (CLA) decreased TNFa, IL-1b and IL-6 and increased levels of antiinflammatory PPARc and IL-10 in a DSS mouse model (Wang et al 2016).…”
Section: Dietary Components Promote Barrier Integrity In Models Of Inmentioning
confidence: 99%